The Development of "Bloodventure" Game Using Computer-Assisted-Instruction for Science Learning on Human Circulatory System - Hengky Kusniar, - (2020)
This research aims to develop bloodventure game by using gamification elements on human circulatory system topics in Junior High School. The method used in this research was developmental research method. The subject of this research is expert and student. Expert chosen in this research are one science expert, one media expert, two science teacher, and one computer teacher. Students chosen in this research are twenty-five students in 8 and 9 grades at one junior high school. The gamification aspects were chosen to make the game were goals, science content, and challenging environment. The expert gave feedbacks in both about their media and the quality of the content aspects. Students were asked about their agreement level of the gamification elements and the effect of gamification. The effect of gamification asked were motivation, Joyness, convenience, addiction, understanding improvement, attractiveness, and interactiveness. The result found that expert gave a good score towards this game. Students also agreed that the game has goals, science content, and challenging environments. The result also found that gamification elements itself caused them to feel motivated, joy, convenience, addiction, improve their understanding, and attracted after playing the game. Other than that, students than half of total students got a score higher than the average score after playing the game